Effect of Completeness of Land Side Facilities on Passenger Satisfaction at Tebelian Sintang Airport, West Kalimantan - Wahyu Tantri Wijaya; Amelia Puspa Tamara (CV. Rayyan Dwi Bharata, 2023)
Airport according to Annex 14 of ICAO (International Civil Aviation Organization) is a certain area on land or water (including buildings, installations and equipment) which is intended either in whole or in part for the arrival, departure and movement of aircraft. Tebelian Sintang Airport is categorized as a new airport so that the buildings and facilities at the airport are still inadequate so that repairs and additional facilities are needed. From the results of observations, researchers know that at Tebelian Sintang Airport, West Kalimantan, they have started to improve (1) existing facilities at the airport and add (2) complete facilities such as special places for breastfeeding, prayer rooms and additional seats for passengers and the addition of other facilities for comfort and safety. passengers while at Tebelian Sintang Airport, West Kalimantan. The research method used is a quantitative method. With a total sample used in this study of 100 respondents, and a total population of 75,000 passengers. The respondents in this study were service users who had used the facilities at Tebelian Sintang Airport, West Kalimantan. Research techniques based on the philosophy of positivism, are used to examine certain populations or samples. Sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/statistical in nature with the aim of testing established hypotheses. This study has one independent variable Facility (X) and dependent variable Passenger satisfaction (Y). The results in this study show that the value of T count is 28.814 T table 1.98447, and a significance value (sig) of 0.000 0.05. Therefore it can be concluded that Ho is accepted, meaning that there is a positive influence of the completeness of the facilities variable on passenger satisfaction at Tebelian Sintang Airport, West Kalimantan.